Likelihood of missed and recurrent adenomas in the proximal versus the distal colon. - Laiyemo,AO; Doubeni,C; Sanderson,AK; Pinsky,PF; Badurdeen,DS; Doria-Rose,VP; Marcus,PM; Schoen,RE; Lanza,E; Schatzkin,A; Cross,AJ (Gastrointest Endosc, 2011)
BACKGROUND: Colonoscopy may be less efficacious in reducing colorectal cancer mortality in the proximal compared with the distal colon. A greater likelihood for missed and recurrent adenomas in the proximal colon may contribute to this phenomenon. OBJECTIVE: To examine whether a proximal adenoma is associated with the risk and location of missed and recurrent adenomas. DESIGN: Prospective. SETTING: Polyp Prevention Trial. PARTICIPANTS: A total of 1864 patients with an adenoma at baseline underwent a follow-up colonoscopy 4 years later (adenoma recurrence). Of these, 1731 underwent a clearing colonoscopy 1 year after the baseline examination (missed adenoma). MAIN OUTCOME MEASUREMENTS: Association of baseline adenoma location with the risk and location of adenomas found at colonoscopy performed 1 year and 4 years later. RESULTS: At the year 1 colonoscopy, 598 patients (34.6%) had an adenoma (missed adenoma). Compared with those with a distal-only adenoma at baseline, patients with a proximal-only adenoma at baseline were more likely to have any missed adenomas (relative risk [RR] 1.28; 95% CI, 1.09-1.49) and a proximal-only missed adenoma (RR 2.05; 95% CI, 1.49-2.80). At the year 4 colonoscopy, 733 patients (39.3%) had adenoma recurrence. Patients with a baseline proximal-only adenoma were more likely to have any adenoma recurrence (RR 1.14; 95% CI, 1.00-1.31) and a proximal-only adenoma recurrence (RR 1.52; 95% CI, 1.15-2.02). Sensitivity analyses involving missed adenomas did not materially affect the risk or location of recurrent adenomas at year 4 colonoscopy. LIMITATION: Lesions may still be missed on repeated colonoscopies. CONCLUSIONS: Missed and recurrent adenomas are more likely to be in the proximal colon.